Markets and morals : justifying kidney sales and legalizing prostitution - Ng, Yew-Kwang (Cambridge : Cambridge University Press, 2019)
Considering efficiency, equality, and morality, this book argues for qualified market expansion, particularly in legalizing kidney sales and prostitution. Legalizing prostitution will benefit both men and women, as argued in a chapter jointly written with Yan Wang. Blood donation without monetary compensation can still result in adequate blood supply if schools educate children that blood donation can actually benefit a donor's health. As a society becomes more advanced, with higher incomes and a better educated populace, more activities can be subject to market exchange, with gradual popular acceptance. Without serious misinformation and irrationality, inequality/fairness as such cannot be a valid reason for limiting the scope of the market. The book supports the use of markets to increase efficiency while also increasing the effort to promote equality, making all income groups better off.
Title from publisher's bibliographic system (viewed on 20 Feb 2019).
Keywords: Economics -- Moral and ethical aspects; Capitalism -- Moral and ethical aspects